PENGETAHUAN DAN SIKAP MASYARAKAT MEMBUANG AIR LIMBAH RUMAH TANGGA DAN KETERSEDIAAN SALURAN PEMBUANGAN AIR LIMBAH (SPAL) DI DESA TANJUNGBERLIAN BARAT, KARIMUN KEPULAUAN RIAU: Description of Knowledge and Attitude of People to Dispose of Household Waste Water and Availability of SPAL in Tanjungberlian Barat Village, Karimun Riau Islands - Samosir, Kholilah; Wulansari, Asih; Yuhesti, Mutia (Poltekes Kemenkes Tanjungpinang, 2022)
Waste from human daily activities that use water is categorized as household wastewater, which consists of kitchen waste, bathing, washing, and house cleaning. The impact on the environment can cause water and soil pollution. Tanjungberlian Barat Village is a village that does not have a wastewater management system to manage wastewater. The purpose of this study was to describe the knowledge and attitudes of the community in disposing of household wastewater and the availability of SPAL in Tanjungberlian Barat Village, Karimun Regency. The type of research used is descriptive observation method with quantitative research design. Research data collection using questionnaire sheets and checklist sheets, the sample used in this study amounted to 88 respondents, the determination of the sample using proportional random sampling technique. Data analysis is univariate and presented in the form of tables and narratives. The results showed that public knowledge was in the bad category as many as 49 people (55.7%), attitudes were in the negative category as many as 47 people (53.4%), and the availability of SPAL that did not meet the requirements as many as 73 houses (83.0%). The conclusion in this study is that the knowledge of the people of Tanjungberlian Barat Village in disposing of household wastewater is in the bad category, the attitude of the community is negative and there are still many people who do not have SPAL that meets the requirements. Suggestions for institutions related to health centers to routinely provide counseling on how to properly dispose of household wastewater and the importance of the availability of SPAL, and for further researchers to conduct further research by adding community action variables and researching household wastewater management.